Hadis Sifat Allah: Keunikan Ganjil, Makna dan Tafsir Komprehensif - Ummy Fadillah Barokah; Uswatun Hasanah; Eko Zulfikar (Indonesian Journal of Humanities and Social Sciences, 2023)
This article explores the meaning of the hadith that states that Allah is "odd" and loves the "odd." Through a qualitative research approach and literature analysis, this study concludes that the understanding of this hadith contains deep meaning. Through a qualitative research approach and analysis of the literature, the study concludes that the understanding of this hadith has a deep meaning. Textually, the HadÄ«th underlines the importance of the obedience and piety of Allah's servants to His commands and the Oneness of Allah as the only God who has no partner and deserves to be worshipped. However, in a social context, Allah is inclusive, loving not only the odd-numbered but also the even-numbered ones. It is reflected in His command to worship and His creation, which includes various numbers, odd and even. Therefore, this hadith cannot be used as a guide for achieving individual or group goals. Hopefully, this article can serve as an essential foundation for further research on the meaning of the hadith related to Allah being "odd" and liking "odd". Hence, more in-depth studies using various approaches are needed for a more comprehensive understanding.